ANALISIS YURIDIS (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 264K/PDT.SUS-HKI/2015) TERHADAP PENGHAPUSAN PENDAFTARAN MEREK AKIBAT MEREK TIDAK DIPERGUNAKAN DALAM KEGIATAN PERDAGANGAN - Pastika Jaya, Ketut; Sudiatmaka, Ketut; Sari Adnyani, Ni Ketut (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2020)
This study was conducted in order to know and understand about the cancellation of the brands carried in trading activities in accordance with Act No. 20 of 2016 on the brand and geographical indications. This study is the method of normative research using qualitative descriptive type of approach, the conceptual approach and the approach of the legislation. And then analyzed using the primary legal materials, secondary and tertiary to obtain relevant conclusions to the problems faced. The results showed that the appeal filed by INTER IKEA Systems BV was rejected on the grounds of Law No. 15 of 2001 on the brand, the brand set to be deleted from the list of generic brand if not used for 3 (three) years in a row.